Horizontal grounding system. - Gomes, Chandima (2010)

(untitled)
The present invention provides a horizontal grounding system for electrical power and signal system that is adapted for use in rocky and arid areas. The horizontal grounding system of the present invention comprises a horizontal grounding electrode (15) having an upper portion (13) and a lower portion (14) in which the upper portion (13) receives a first conductive member (1) extending through the lower portion (14), a first backfill material (10) contained in the lower portion and a second backfill material (9) contained in the upper portion (13). The first and second backfil material (9,10) enable the retaining of soil moisture in the vicinity of the horizontal grounding electrode (15) to maintain a high conductivity level of soil and thus facilitate the grounding of electrical charges by utilizing the combination of backfill materials (9,10) in conjunction with the horizontal grounding electrode (15).